Deficit irrigation and biostimulation preconditioning to improve drought resistance in melon - Susana Zapata-García; Abdelmalek Temnani; Pablo Berríos; Pedro J. Espinosa; Claudia Monllor; Alejandro Pérez-Pastor (Agricultural Water Management)
The need to increase crop water productivity under low water availability conditions, leads not only to the use of technology for real-time soil water monitoring, but also to test the response of certain products, such as algae-based biostimulants, on the agronomy and physiology response of the plants. The aim of this study was to assess the effect of different sustainable strategies to maximize water productivity on melon plants, by monitoring the soil water status using sensors, reduce water inputs in a non-critical period of the melon growth and by preconditioning plants to cope with water stress by the application of a commercial biostimulant based on Ascophyllum nodosum extract, Seamac Rhizo®. With special emphasis on understanding the physiological response that these plants develop to respond to water stress. Four treatments were evaluated: (i) a farmer treatment, irrigated at 100 % ETc, (ii) a precision irrigation (PI) treatment, irrigated with a threshold of 20 % soil water depletion in the active root uptake zone, between flowering and ripening, otherwise irrigated as FARM; (iii) an irrigation suppression (IS) treatment, irrigated as PI for the most of the cycle, except between 42 and 55 days after transplant (swelling of the first fruits), when irrigation was totally suppressed; (iv) a biostimulated irrigation suppression treatment (ISb), irrigated as IS with two applications of biostimulant during vegetative development. Our results indicate that under the severe water deficit applied, melon plants did not reduce their marketable yield with respect to the PI treatment due to leaf osmotic adjustment. Moreover, biostimulated plants (ISb) exhibited an enhanced water root absorption, which enabled them to increase their yield by a 44 % compared to IS treatment. This fact increased the irrigation water productivity by 53 % and 44 % with respect to the PI and IS treatments, respectively. Furthermore, harvested fruits from the biostimulated treatment showed a higher concentration of phenolics compounds compared to PI. Therefore, the incorporation of plant biostimulation is proposed as a sustainable strategy to increase water productivity and enhance functional fruit quality.